Contract functions in service exchange governance: evidence from logistics outsourcing. Issue 16 (9th December 2016) - Selviaridis, Kostas
Abstract: The logistics outsourcing literature emphasises relational governance mechanisms and has underplayed the role of formal contractual provisions. This paper empirically examines the multiple functions that contracts perform in the governance of service exchanges. Codification, safeguarding, coordination and adaptation functions are linked to contract specification schedules, payment mechanisms, (early) termination rights, performance review and communication provisions, service variations clauses and renegotiation provisions. Contracts may also embody exchange- or partner-specific learning, albeit to a limited extent. Overall, the empirical findings lend support to the functional view of contracting. The functionality of contracts extends beyond safeguarding against opportunism and financial losses. In addition to offering economic and legal safeguards, contracts are used to coordinate and adapt service exchanges in the face of complexity and uncertainty.